Antihypertensive activity of a quinoline appended chalcone derivative and its site specific binding interaction with a relevant target carrier protein1. Issue 80 (2nd September 2015) - Kumar, Himank; Devaraji, Vinod; Joshi, Ritika; Jadhao, Manojkumar; Ahirkar, Piyush; Prasath, R.; Bhavana, P.; Ghosh, Sujit Kumar
<x xml:space="preserve">Abstract</x> The usefulness of heterocyclic chalcone derivative as a therapeutic target in controlling hypertension and its site specific binding interaction with model transport protein to get a clear picture about its delivery mechanism.